INFLUENCE OF SELECTED FEED ADDITIVES ON THE GROWTH AND GONADAL MATURATION OF GOLDFISH (CARRASSIUS AURATUS) - B. KANNAN; B. AHILAN; STEPHEN SAMPATH; J. KUMAR; S. ATHITHAN (The Bioscan, 2015)
The present investigation was designed to study the influence of selected feed additives, viz., fish meal, shrimp head meal and soy flour on the growth and gonadal maturation of goldfish, Carassius auratus. The feeding trial was carried out for 60 days and the sampling was carried out once in a fortnight. The fish meal, at 30 per cent concentration had the highest mean body weight gain (1.966 g) and specific growth rate (0.320 %/day), which ranked first among all the concentrations tried. The mean body weight gain was five folds higher in 30% concentration when compared to control. In the case of gonadal maturation, the fishes fed with 40% yielded the best results in both male and female. The shrimp head meal, at 40% concentration yielded the best result with regard to the growth of the goldfish. With regard to breeding performance of goldfish fed with different concentration of shrimp head meal diet, 20% concentration yielded the best result followed by 40% concentration. The mean body weight gain of 1.351 g was observed at 30% concentration of soy flour fed fishes. These results indicated that fish meal at 30% concentration is the best for the better growth of goldfish.